Analyzing the Alexithymia Scores of University Students Who Do and Do not Do Sports - Banu Demir; Ali Osman Kıvrak; İlhan Gözen; Dr. Yahya Gökhan Yalçın (Selcuk University, 2021)
This study is conducted to analyze the differences in the alexithymia scores of university students who do and do not do sports. In total, 365 university students participated voluntarily in the study. 189 (106 men and 83 women) of them were licensed for at least 2 years in a team or individual sports branches, and 176 (98 men and 78 women) of them did not do sports. In order to reach the data of the study, the personal information form which is developed by researchers, and the Toronto alexithymia scale with 20 questions developed by Bagby et al. in 1994 (2) and adapted into Turkish by Güleç et al.(10) have been used. According to the results of the research, no significant differences were found in the total alexithymia scores and the sub-dimensions of Difficulty in Recognizing Emotions, Difficulty in Expressing Emotions, and Extraverted Thinking in accordance of the gender of university students who do and do not do sports.